The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0100-879x1997000100005
|View full text |Cite
|
Sign up to set email alerts
|

Complications of surgical treatment of cervical carcinoma

Abstract: A total of 302 patients with stage Ib and IIa cervical carcinoma were submitted to radical hysterectomy and lymphadenectomy during the period from 1980 to 1994. The morbidity rate was 37.5% and the mortality rate 0.6%. The most common intraoperative complications were injuries to the great pelvic vessels and the most frequent postoperative complications involved the urinary tract. The leading causes of morbidity were urinary infection (20.8%), bladder dysfunction (9.2%) and ureteral fistulas (2.9%). Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…In our study, the only fistula occurred in a patient who had received 5000 cGy radiotherapy before radical surgery, and with continuous bladder drainage for 3 weeks there was spontaneous healing of the fistula. The incidence of urinary tract infection (UTI) in our series was 11% by 14 weeks after surgery and this was comparable to that reported by Cardosi [8] but less than the figure of 20% documented by Abrao [9]. Also, Chen reported a 14% urinary tract infection rate following radical surgery [10].…”
Section: Discussionsupporting
confidence: 84%
“…In our study, the only fistula occurred in a patient who had received 5000 cGy radiotherapy before radical surgery, and with continuous bladder drainage for 3 weeks there was spontaneous healing of the fistula. The incidence of urinary tract infection (UTI) in our series was 11% by 14 weeks after surgery and this was comparable to that reported by Cardosi [8] but less than the figure of 20% documented by Abrao [9]. Also, Chen reported a 14% urinary tract infection rate following radical surgery [10].…”
Section: Discussionsupporting
confidence: 84%
“…In addition to the aforementioned complications, genitourinary fistulas are also significant due to their clinical consequences following radical hysterectomies. The reported rate of fistulas has been as high as 30% [21], possibly due to the more extensive parametrial resection that was commonly performed. However, more recent studies have shown a decrease in the fistula rate to under 3% [18,19,22], consistent with our cohort's findings (2.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other complications secondary to radical hysterectomies, genitourinary stulas are also important due to their clinical consequences. The rate of stula has been reported to be up to 30% [22], probably due to the more extensive parametrial resection that was routinely performed in the past. The most recent studies showed a stula rate under 3% [18, 21,23,24], which is similar to what was found in our cohort (2.7%).…”
Section: Discussionmentioning
confidence: 99%